(untitled) (Revista de História Regional, 2025)
This article analyses Kerbfest, a celebration that takes place in the municipality of Seara in the western region of Santa Catarina, Brazil. This party started in Seara in 1993 and continues to the present. It is organised by the German-Brazilian group together with the Evangelical Church of the Lutheran Confession in Brazil. The time frame analysed was 1993 to 2005 and the sources observed were meeting minutes, audiovisual recordings, photographs, newspapers, and interviews. Analysing the sources allowed us to see that Kerbfest is a festivity built in Brazil and not a Germanic heritage brought by immigrants. The festival has representations of a collectivity, portraying not just the municipality of Seara, but various localities that went through the processes of German immigration that wanted to build bonds of belonging and identity.